SINIS-LA Method for IT Alignment Considering Service Level Management - Ferreira, Eduardo; Trinkenreich, Bianca; Barcellos, Monalessa Perini; Santos, Gleison (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2021)
Background: Organizations have to align a wide variety of organizational goals and strategies to achieve business goals, growth, and survive. In addition to ensuring the alignment between strategies in place and indicators with business goals, IT service organizations must keep the quality of service by fulfilling Service Level Agreements (SLA) sealed with their clients. Objective: We present SINIS-LA, which supports elicitation, alignment, and monitoring of business goals, indicators, and strategies focused on controlling SLA of the IT services provided. Method: We created SINIS-LA by applying Design Science Research (DSR). Results: SINIS-LA was used by the IT service management team at an IT service organization. By using SINIS-LA the team achieved IT alignment and monitored it. SINIS-LA was considered applicable for identifying, reviewing, and monitoring service goals, strategies, indicators, and related SLA. Conclusion: The results showed evidence that SINIS-LA supports the definition and monitoring of the alignment of goals, strategies, indicators, and SLA in an IT service organization.